Secukinumab administration by pre‐filled syringe: efficacy, safety and usability results from a randomized controlled trial in psoriasis (FEATURE). (11th December 2014) - Blauvelt, A.; Prinz, J.C.; Gottlieb, A.B.; Kingo, K.; Sofen, H.; Ruer‐Mulard, M.; Singh, V.; Pathan, R.; Papavassilis, C.; Cooper, S.; the FEATURE Study Group
Summary Background Secukinumab, a fully human anti‐interleukin‐17A monoclonal antibody, demonstrated efficacy and safety in moderate‐to‐severe plaque psoriasis when administered via subcutaneous injection. Self‐administration by pre‐filled syringe (PFS) can offer patients clinical benefits of a drug, with increased convenience. Objectives To assess efficacy, safety and usability of secukinumab administration via PFS in subjects with moderate‐to‐severe plaque psoriasis. Materials and methods Subjects in this phase 3 trial were randomized 1 : 1 : 1 to secukinumab 300 or 150 mg or matching placebo. Results to week 12 are presented here. Each treatment was delivered using a PFS once weekly to week 4, and again at week 8. Co‐primary endpoints were secukinumab superiority over placebo for week 12 PASI 75 (≥ 75% reduction in Psoriasis Area and Severity Index) and IGA mod 2011 (2011 modified Investigator's Global Assessment) 0/1 response rates. Secondary endpoints included PFS usability, determined by observer rating of successful, hazard‐free self‐injection and subject rating of acceptability by the Self‐Injection Assessment Questionnaire (SIAQ). Results Co‐primary endpoints were met, with demonstration of superiority for each secukinumab dose vs. placebo at week 12 (PASI 75: 75·9%, 69·5% and 0% for secukinumab 300 mg, 150 mg and placebo; IGA mod 2011 0/1: 69·0%, 52·5% and 0%, respectively; P < 0·0001 for all comparisons vs. placebo). PFS usability was high: 100% of subjects successfully self‐administered treatment at week 1, and subjects reported high SIAQ‐assessed acceptability of the PFS throughout the trial. No new/unexpected safety signals were observed. Conclusions Secukinumab administration by PFS was effective, with an acceptable safety profile and high usability. The PFS provides a reliable, convenient form of secukinumab administration in subjects with moderate‐to‐severe plaque psoriasis.